A Visible‐Light‐Driven Iminyl Radical‐Mediated C−C Single Bond Cleavage/Radical Addition Cascade of Oxime Esters. Issue 3 (18th December 2017) - Yu, Xiao‐Ye; Chen, Jia‐Rong; Wang, Peng‐Zi; Yang, Meng‐Nan; Liang, Dong; Xiao, Wen‐Jing
Abstract: A room‐temperature, visible‐light‐driven N‐centered iminyl radical‐mediated and redox‐neutral C−C single bond cleavage/radical addition cascade reaction of oxime esters and unsaturated systems has been accomplished. The strategy tolerates a wide range of O‐acyl oximes and unsaturated systems, such as alkenes, silyl enol ethers, alkynes, and isonitrile, enabling highly selective formation of various chemical bonds. This method thus provides an efficient approach to various diversely substituted cyano‐containing alkenes, ketones, carbocycles, and heterocycles. Abstract : A visible‐light‐driven room‐temperature N‐centered iminyl radical‐mediated and redox‐neutral C−C single bond cleavage/radical addition cascade reaction of oxime esters and unsaturated systems has been accomplished. The strategy tolerates a wide range of O‐acyl oximes and alkenes, silyl enol ethers, alkynes, and isonitrile. This method allows access to various cyano‐containing alkenes, ketones, carbocycles, and heterocycles.